Artia Sipaha Sada: Hari Pertama Bulan Pertama Etnik Batak Toba - Febryanto Malau; Erlin Nainggolan; Rimma Natasari Sitanggang; Murni Eva Rumapea; Pittauli Ambarita (Umbara, 2022)
This study aims to describe the meaning of Artia Sipaha Sada, a ceremony to celebrate the first day in the first month of the Batak Toba ethnic group by Parmalim believers. This study applied a qualitative method and took place at Tomok Village, Samosir District and Huta Tinggi Village, Toba Regency. Data was collected through interviews and archival study and was analyzed using Atlas.ti software. The results of this study suggests that Artia Sipaha Sada, celebrated on the first day of the first month in the Batak Toba ethnic calendar, has a similar meaning to the new year in the Gregorian calendar or other ethnic calendars. Sipaha Sada is one of the ceremonies held by Parmalim to commemorate the birthday of Simarimbulubosi as well as occasion to start a new day. It begins with a ritual to contemplate the previous year. Today,  Artia Sipaha Sada is also celebrated by non Parmalim with some adjustments according to the beliefs of the celebrants.